Substructural components in the sporoderm of the Family Cyatheaceae - Marquez, Gonzalo Javier (2015)
The ultrastructure of the sporoderm of three genera of the Family Cyatheaceae was studied in detail, with the aim to elucidate its constituent elements. While the perispore of Alsophila and Sphaeropteris is thick and complex, that of Cyathea is reduced and with a different structure; nevertheless, their basic elements seem to be similar. We found that the substructural components are threads with a diameter of 50-100 nm and that each one is composed of an inner channel, around which there are several smaller coiled units. The channels are interconnected and form a complex system, which is continuous within the exospore and in a similar pattern. This network of threads could be related to the transfer of substances between the outer and inner parts of the spores during their development.